Sistem Rekomendasi Lowongan Pekerjaan Untuk Fresh Graduate Menggunakan Metode Weighted Product Berbasis Android - Dwi Astuti; Aryo Pinandito; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Recommendation System is a software or technique that provides suggestions for items or objects which can be used for some users. That recommendation is related with any decision making process, such as items that would be chosen, etc. In this research, recommendation system will be used to decide which job vacancies that match with user's criteria. Currently, there are many websites that provide job vacancy's information, but it's still difficult to find system that can recommend any job vacancies that match user's criteria yet. A recommendation system was made which use one of Multi-Criteria Desicion Making (MCDM), Weighted Product method. Criteria that are used for this method are last education or degree, GPA, age, English skill, and days remaining before the vacancy closed. Meanwhile, data that are used as alternatif are job vacancy's data which obtained from job vacancy's websites and some brochure, To use this system, user only need to choose criteria that match with user's criteria. The output that are diplayed by this system are job vacancies list which already be sorted based on the method's calculation. User can also see job vacancy's information more detailed. The result from accuration test that had been done is 17,5%. Keywords: recommendation, system, job, vacancy, weighted, product